Successful use of a fully closed-loop insulin delivery system in an adolescent with diabetes secondary to pancreatitis – a case report - Abirami Namasivayam; Sandra Walton-Betancourth; Helen Hysted; Vipan Datta; Cliodhna Myles; Charlotte Boughton; M. Loredana Marcovecchio; Ajay Thankamony (Annals of Pediatric Endocrinology & Metabolism)
Variable rate intravenous insulin infusion (VRIII) is often administered to hospitalized patients with diabetes, who are unwell and have complex nutritional needs. However, VRIII is a reactive approach to insulin delivery that is not based on physiology, is associated with significant safety concerns, and is extremely resource intensive. Fully closed-loop (FCL) systems are promising technologies in diabetes management. CamAPS HX is one of these systems that improves glycemic outcomes in adults, but evidence of its effectiveness and safety in children is lacking. In this report, we present a case of a 14-year-old adolescent who developed diabetes secondary to acute necrotizing pancreatitis and was associated with complications that included esophageal perforation and peripancreatic collections. He was initially treated with VRII to manage total parenteral nutrition (TPN) before transitioning to nasogastric tube feeding. However, variable tolerance to nasogastric feeds and frequent titration of TPN posed significant challenges to insulin therapy. Therefore, the CamAPS HX FCL system was initiated which allowed maintenance of stable glucose levels without hypoglycemia during the gradual transition from TPN to enteral nutrition. This case provides evidence that use of FCL systems is safe and effective for management of inpatient children and adolescents with diabetes and complex nutritional needs. To our knowledge, this is the first reported case of a pediatric inpatient in whom diabetes was managed using an FCL system.